Evaluasi Kritis terhadap Paham Mazmur Kutukan di tengah-tengah Fenomena Problem Etis terhadap Mazmur 83:1-19 [A Critical Evaluation of the Understanding of the Curse and Ethical Problems in Psalm 83:1-19] - Hia, Lurusman Jaya (Universitas Pelita Harapan, 2023)
The idea of man’s belief in curses poses a problem for the curse Psalms. Among believers, there is a misunderstanding of the curse in Psalm 83:1-19. A critical evaluation is needed to correctly understand this curse Psalm because it contains complex life values. Critical evaluation is part of the resolution process of ethical problems in the lives of believers. Therefore, the purpose of this study is to offer a critical evaluation of the understanding of this curse Psalm amidst the issue of ethical problems in the lives of believers so that every believer knows the intention of the Psalmist in the actualization of human morals. The result of this study shows that the Psalmist offers his prayers to punish his enemies in order to demonstrate God’s justice, truth, and mighty work over the sin of man. Instead of hoping his enemies will be punished, the Psalmist emphasizes God’ s love. With this understanding, believers should be enriched knowing God’s love and punishment are not contradictory. The method used in this study is a literature review. BAHASA INDONESIA ABSTRACT: Gagasan tentang kepercayaan manusia pada kutukan menimbulkan masalah bagi Mazmur terkutuk. Dalam kehidupan orang percaya, masalah kesalahpahaman tentang kutukan muncul menurut Mazmur 83:1-19. Tak jarang, evaluasi kritis membahas pemahaman Mazmur kutukan yang benar karena Mazmur terkutuk ini mengandung nilai-nilai kehidupan yang begitu kompleks. Evaluasi kritis adalah bagian dari wahyu yang menciptakan masalah etika dalam kehidupan orang percaya. Oleh karena itu, tujuan dari penelitian ini adalah untuk memberikan evaluasi kritis terhadap pemahaman Mazmur terkutuk di tengah fenomena masalah etika dalam kehidupan orang percaya. Sehingga setiap orang percaya mengetahui tujuan seorang pemazmur dalam aktualisasi moral Tuhan melalui penelitian ini. dan memperkaya pemahaman gereja tentang Mazmur terkutuk yang jarang dipahami dengan benar.